2021
DOI: 10.1063/5.0039979
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress on 2D magnets: Fundamental mechanism, structural design and modification

Abstract: The two-dimensional (2D) magnet, a long-standing missing member in the family of 2D functional materials, is promising for next-generation information technology. The recent experimental discovery of 2D magnetic ordering in CrI3, Cr2Ge2Te6, VSe2, and Fe3GeTe2 has stimulated intense research activities to expand the scope of 2D magnets. This review covers the essential progress on 2D magnets, with an emphasis on the current understanding of the magnetic exchange interaction, the databases of 2D magnets, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
190
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 267 publications
(211 citation statements)
references
References 512 publications
4
190
0
1
Order By: Relevance
“…[ 10 ] From the observed change in resistivity at 80−120 K, the Curie temperature of those flakes was estimated to be ≈80 K. [ 10 ] This remarkable increase from the bulk value of 33 K [ 6,7,11 ] is in stark contrast to the behavior of other 2D ferromagnets and has been proposed to stem from the increased intralayer superexchange interaction via Te in the few‐layer limit. [ 9,12 ] Recently, in the ultrathin layer limit, the thickness‐dependent magnetic transition from 3D (Heisenberg) to 2D Ising behavior has been observed for a CrSiTe 3 thickness of ≈7 nm, which goes hand in hand with a drop in Curie temperature from 33 to 17 K. [ 13 ] This behavior is often tied to the strong dependence of the electronic structure on the reduced dimensionality in the ultrathin layer limit, as it has been experimentally observed for CrI 3 . [ 1 ]…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…[ 10 ] From the observed change in resistivity at 80−120 K, the Curie temperature of those flakes was estimated to be ≈80 K. [ 10 ] This remarkable increase from the bulk value of 33 K [ 6,7,11 ] is in stark contrast to the behavior of other 2D ferromagnets and has been proposed to stem from the increased intralayer superexchange interaction via Te in the few‐layer limit. [ 9,12 ] Recently, in the ultrathin layer limit, the thickness‐dependent magnetic transition from 3D (Heisenberg) to 2D Ising behavior has been observed for a CrSiTe 3 thickness of ≈7 nm, which goes hand in hand with a drop in Curie temperature from 33 to 17 K. [ 13 ] This behavior is often tied to the strong dependence of the electronic structure on the reduced dimensionality in the ultrathin layer limit, as it has been experimentally observed for CrI 3 . [ 1 ]…”
Section: Introductionmentioning
confidence: 96%
“…[ 5 ] It is important to note that despite their close similarities such as their ferromagnetic bulk properties (in contrast to the prediction of CrSiTe 3 being an antiferromagnet), [ 6–8 ] the very different magnetic properties of CrSiTe 3 compared with CrGeTe 3 monolayers are due to minute differences in their second‐ and third‐nearest neighbor exchange interactions, [ 5 ] the larger van der Waals (vdW) gap, and the smaller Cr−Cr distance. [ 9 ] Also, while the interlayer coupling in CrSiTe 3 is antiferromagnetic, the intralayer coupling is ferromagnetic, and the overall properties of the material therefore strongly depend on the c ‐axis lattice constant. [ 5 ] The thickness dependence of the magnetic properties of CrSiTe 3 , down to single‐ and few‐monolayer flakes, has been investigated via Hall measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, the intrinsic ferromagnetism of 2D magnets was only detected in low-temperature conditions, which was a significant step forward. In 2018, O'Hara et al observed ferromagnetism in MnSe x films grown by MBE at room temperature [6,7]. A representative metal 2D magnet is represented by the monolayerr VSe 2 , which exhibits charge density wave and magnetic phenomena at the same time.…”
Section: Molecular Beam Epitaxy (Mbe)mentioning
confidence: 99%
“…38,39 Additional terms, such as the DM interaction and the magnetocrystalline anisotropy energy (MCAE), arise from both spin-orbit coupling and the underlying symmetry of the compound. 40,41 In this section, we introduce the terms thought to be most relevant to magnetic ordering in Fe-and Cr-intercalated NbS 2 and TaS 2 , namely the RKKY interaction, the DM interaction, and MCAE. Excellent general introductions to magnetism in extended solids can be found elsewhere.…”
Section: Origins Of Magnetic Behaviormentioning
confidence: 99%